Impact of Orthodontic-Surgical Treatments on the Signs and Symptoms of Temporomandibular Disorders: A Systematic Review - Elodie Ehrmann; Marie Bernabeu; Yannick Tillier; Julien Camia; Corentin Ecalle; Charles Savoldelli; Carole Charavet (MDPI AG, 2024)
Introduction: Some patients exhibit temporomandibular joint or muscular disorders of the masticatory system before, during, or after orthognathic surgery (OS). These are collectively referred to as temporomandibular disorders (TMDs). This systematic literature review aimed to determine the relationship between orthodontic-surgical treatment and TMDs. Methods: An electronic search of the PubMed database, supplemented by a manual search, was performed; the search included any studies published between 2021 (date of the last search in a systematic review of the literature on the subject) and June 2023 that evaluate the prevalence of TMDs during orthodontic-surgical treatment. The diagnosis of TMDs had to be established using the diagnostic algorithm "diagnostic criteria for temporomandibular disorders (DC/TMDs)", and the diagnosis of disc displacement had to be confirmed using magnetic resonance imaging (MRI). The data were extracted and statistically analyzed. Results: Of the 100 results, seven eligible articles were included, representing a total of 529 cases undergoing orthodontic-surgical treatment. A reduction in joint noises (64.8%), arthralgia (57 to 77%), and myalgia (73 to 100%) was found after orthodontic-surgical treatment despite the fact that a minority of patients exhibited these signs and symptoms even though they were asymptomatic before treatment. The effects of OS on disc position were objectively unpredictable. After surgery, the presence of headaches decreased without significance and the risk of their occurrence was very low (1%). The studies converged toward a reduction in the amplitudes of mouth opening and lateral/protrusion movements. Finally, after the treatment, mandibular function was improved. Conclusion: Under the conditions of this study, OS seems to have a positive impact on the signs and symptoms of TMDs; however, it is not possible to predict the consequential effects on the position of the TMJ disc, whether it is initially in a normal position or displaced.